2016
DOI: 10.1245/s10434-016-5571-y
|View full text |Cite
|
Sign up to set email alerts
|

Poor Prognosis After Second Locoregional Recurrences in the CALOR Trial

Abstract: Purpose Isolated locoregional recurrences (ILRR) of breast cancer confer a significant risk of developing distant metastasis. Management practices and second-ILRR events in the CALOR trial are investigated. Methods 162 patients with ILRR were randomly assigned to receive post-operative chemotherapy, or no chemotherapy. Descriptive statistics characterize outcomes according to local therapy and the influence of hormone receptor status on subsequent recurrences. Competing risk regression models, Kaplan-Meier e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Follow‐up data for patients with ipsilateral locoregional recurrences in the CALOR trial were reported recently: 9·3 per cent of patients developed an isolated locoregional re‐recurrence after 5 years and 23 per cent developed DR. However, the CALOR trial included patients with an isolated IBTR as well as those with regional disease.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Follow‐up data for patients with ipsilateral locoregional recurrences in the CALOR trial were reported recently: 9·3 per cent of patients developed an isolated locoregional re‐recurrence after 5 years and 23 per cent developed DR. However, the CALOR trial included patients with an isolated IBTR as well as those with regional disease.…”
Section: Discussionmentioning
confidence: 93%
“…Ipsilateral breast tumour recurrence (IBTR) has an unfavourable prognosis, with a significant risk of subsequent local, regional and distant recurrence as well as poor survival. The 5‐year overall survival rate for patients with IBTR ranges between 45 and 80 per cent.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that sLRR not only reduced the quality of life, but also portended an unfavorable survival outcome ( 5 , 16 ). Our results showed that 50.2% of patients developed sLRR, among which sRR accounted for 50.5%.…”
Section: Discussionmentioning
confidence: 96%
“…Hence, breast preservation should always be considered and offered after careful evaluation and appropriate patient selection [ 25 ]. However, second BCS alone is associated with a significantly higher rate of second IBTR compared with sMT [ 26 , 27 ], which is in turn associated with poor prognosis [ 7 , 28 ]. Combination of repeat breast conservation with a second course of radiotherapy as APBI is reducing the increased risk of second IBTR compared with second BCS alone, yielding similar oncological outcomes to sMT [ 8 ].…”
Section: Discussionmentioning
confidence: 99%